Unwelcome Return Home: Jews, Anti-Semitism and the Housing Problem in Post-War Kyiv - Khiterer Victoria (Eastern European Holocaust Studies, 2022)
The article discusses the aftermath of the Holocaust in Kyiv and shows what factors contributed to the sharp rise of state and popular anti-Semitism in the city in the post-war years. During the Nazi occupation, Babyn Yar in Kyiv became one of the largest Holocaust killing grounds, where the Nazis and their local collaborators exterminated almost all Jews who remained in the city. When surviving Jews returned to Kyiv from evacuation and the fronts, gentiles frequently refused to hand over apartments to the pre-war occupants. Jewish appeals to the authorities often were denied. The authorities, many of whom shared the anti-Semitic mood of much of the local population, usually refused to help returning Jews claim their property. A Jewish pogrom broke out in Kyiv in September 1945, when sixteen Jews were killed and over 100 injured. The harshness of life in the ruined city, the severe shortage of apartments and the rise of the anti-Semitism overlapped in Kyiv and brought about an explosion of anti-Jewish violence in the city. The Soviet authorities attempted to suppress popular anti-Semitism in Ukraine after the war but failed. Then they adopted the policy of state anti-Semitism in 1948–1953.